Hybrid Monte Carlo method for condensed-matter systems - Mehlig, Bernhard; Heermann, Dieter W.; Forrest, Bruce M. (Physical review. B, Condensed matter and materials physics, 1992)
In this paper the static properties of the hybrid Monte Carlo algorithm are studied in the context of condensed-matter systems. The algorithm is used to simulate a Lennard-Jones liquid near the coexistence region. The hybrid Monte Carlo algorithm generates a canonical distribution in configuration space, permitting the application of the Ferrenberg-Swendsen extrapolation scheme. Moreover, it is an exact algorithm: The configurational averages prove to be independent of the step size, and the algorithm does not suffer from numerical instabilities due to finite step size.